Copy number loss in the region of the ASPN gene in patients with acetabular dysplasia: ASPN CNV in acetabular dysplasia. Issue 7 (July 2017) - Sekimoto, T.; Ishii, M.; Emi, M.; Kurogi, S.; Funamoto, T.; Yonezawa, Y.; Tajima, T.; Sakamoto, T.; Hamada, H.; Chosa, E.
Abstract : Objectives: We have previously investigated an association between the genome copy number variation (CNV) and acetabular dysplasia (AD). Hip osteoarthritis is associated with a genetic polymorphism in the aspartic acid repeat in the N-terminal region of the asporin ( ASPN ) gene; therefore, the present study aimed to investigate whether the CNV of ASPN is involved in the pathogenesis of AD. Methods: Acetabular coverage of all subjects was evaluated using radiological findings (Sharp angle, centre-edge (CE) angle, acetabular roof obliquity (ARO) angle, and minimum joint space width). Genomic DNA was extracted from peripheral blood leukocytes. Agilent's region-targeted high-density oligonucleotide tiling microarray was used to analyse 64 female AD patients and 32 female control subjects. All statistical analyses were performed using EZR software (Fisher's exact probability test, Pearson's correlation test, and Student's t -test). Results: CNV analysis of the ASPN gene revealed a copy number loss in significantly more AD patients (9/64) than control subjects (0/32; p = 0.0212). This loss occurred within a 60 kb region on 9q22.31, which harbours the gene for ASPN . The mean radiological parameters of these AD patients were significantly worse than those of the other subjects (Sharp angle, p = 0.0056; CE angle, p = 0.0076; ARO angle, p = 0.0065), and all nine patients required operative therapy such as total hip arthroplasty or pelvic osteotomy. Moreover, six of these nine patients had a history of operative or conservative therapy for developmental dysplasia of the hip. Conclusions: Copy number loss within the region harbouring the ASPN gene on 9q22.31 is associated with severe AD. A copy number loss in the ASPN gene region may play a role in the aetiology of severe AD. Cite this article: T. Sekimoto, M. Ishii, M. Emi, S. Kurogi, T. Funamoto, Y. Yonezawa, T. Tajima, T. Sakamoto, H. Hamada, E. Chosa. Copy number loss in the region of the ASPN gene in patients with acetabular dysplasia: ASPN CNV in acetabular dysplasia. Bone Joint Res 2017;6:439–445. DOI: 10.1302/2046-3758.67.BJR-2016-0094.R1.